(3MGTjI Ydi GHf UOQ GdOjfs - (3Ydj Hf UOQ GdOjf Hf YUGe GdOjfs; (3Ydj Hf UOQ GdOjf Hf YUGe GdOjfs
(3ChdgG (B:s
(3ajbhd GdYHO GdabjQ Edi CdWGa QH GdYGdejf s
(3BNQgG (B:s
(3hdGjNai Cf Chai bhdg EfeG gh GdeGOI Ch GdgjFg defY GdNdh hEdG abO s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGfjIs
(3GdGSJYGQGJ eYGfi GdGSJYGQGJ ddSeQbfOis
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdadSaI hGdefWbs